Feasibility of NepaDengue mobile application for dengue prevention and control: user and stakeholder perspectives in Nepal - Eggi Arguni; Anita Mahotra; Yuvraj Pokhrel; Tulsi Ram Thapa; Riris Ahmad Andono (BMJ Public Health)
Background Dengue has emerged as a significant public health issue in Nepal since 2006, necessitating innovative approaches to disseminating timely information and promoting preventive behaviour. Our study focuses on developing and pretesting a mobile health app called NepaDengue, assessing its acceptance and factors influencing its implementation.Methods A concurrent triangulation mixed-method design was used, and an intervention was conducted among 228 university students using the mobile application. Acceptability was assessed using the technology acceptance model (TAM) based on user experiences over 1 week. Focus group discussions among students and female community health volunteers and key informant interviews among key dengue stakeholders were conducted to explore facilitators and barriers. Descriptive statistics were calculated, and a thematic analysis was conducted.Results The high acceptability mean rating scores reported based on the TAM construct indicate that the application is perceived as useful and easy to use and exhibits good functioning and gestural design. The use of the NepaDengue application for dengue prevention and control activities has been perceived as acceptable by users and stakeholders. However, specific barriers were identified, including concerns about sustained usability, illiteracy and limited access to the internet and smartphones. We suggested promoting the application, fostering government ownership and encouraging collaboration to enhance its reach and effective implementation.Conclusions The NepaDengue application has been perceived as a promising tool for dengue prevention and control in Nepal. Further piloting and implementation of the app in the community setting is recommended.